2018
DOI: 10.14745/ccdr.v44i78a02
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of hepatitis C among health care providers and the public: A scoping review

Abstract: Background: The Global Viral Hepatitis Strategy aims to eliminate hepatitis as a public health threat by 2030. The hepatitis C virus (HCV) can be difficult to detect as infection can remain asymptomatic for decades. Individuals are often neither offered nor seek testing until symptoms develop. This highlights the importance of increasing awareness and knowledge among health care providers and the public to reach the viral hepatitis goals. Objectives: To conduct a scoping review to characterize current awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…3,6,14,19,20 A recent study in Nigeria showed a relationship between HBV vaccination and knowledge about viral hepatitis, 17 suggesting an unmet need to improve knowledge about HBV to increase HBV vaccination uptake, particularly in older adults. Moreover, in this study, we observed a general local misperception that a vaccine is available for HCV, which has been similarly observed globally, 18,21 although we observed a slightly higher local awareness rate (19.0%) than that in Singapore (15.0%). 18 This lack of awareness pertaining to HCV might impede the adoption of correct preventive measures against hepatitis C infection.…”
Section: Discussionsupporting
confidence: 68%
“…3,6,14,19,20 A recent study in Nigeria showed a relationship between HBV vaccination and knowledge about viral hepatitis, 17 suggesting an unmet need to improve knowledge about HBV to increase HBV vaccination uptake, particularly in older adults. Moreover, in this study, we observed a general local misperception that a vaccine is available for HCV, which has been similarly observed globally, 18,21 although we observed a slightly higher local awareness rate (19.0%) than that in Singapore (15.0%). 18 This lack of awareness pertaining to HCV might impede the adoption of correct preventive measures against hepatitis C infection.…”
Section: Discussionsupporting
confidence: 68%
“…40,41 Like HBV, HCV is also a blood-borne disease; however, there is currently no available vaccine to prevent HCV, which remains a common misperception globally. 42 Instead, the recent development of oral DAA treatment regimens for HCV resulted in a successful initial cure rate of up to 99% with minimal side effects, prompting a step closer towards WHO's viral HCV eradication goal. 43,44 Although HCV prevalence in Singapore is estimated to be 300 times lower than HBV, 7 the inadequate knowledge and awareness of HCV transmission risks could inadvertently impede measures taken to reduce transmission or undertake treatment within the community, 45 especially among high-risk groups such as persons who inject drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Even after learning about a history of drug abuse or other risk factors, only about 80% of PCP order tests for HCV infection 12 . This could be explained by PCP having poor knowledge about hepatitis C transmission, epidemiology and associated risk factors, which have been described in other studies, along with time constraints and lack of comfort discussing HCV 18,19 . Research indicates that offering PCP training on the epidemiology, diagnosis and management of HCV infection would increase HCV testing and would be cost‐effective 20 …”
Section: Discussionmentioning
confidence: 99%
“…12 This could be explained by PCP having poor knowledge about hepatitis C transmission, epidemiology and associated risk factors, which have been described in other studies, along with time constraints and lack of comfort discussing HCV. 18,19 Research indicates that offering PCP training on the epidemiology, diagnosis and management of HCV infection would increase HCV testing and would be cost-effective. 20 At 0.67 [CI: 95%, 0.65-0.70], the seroprevalence of HCV infection in 2016 was consistent with the estimated prevalence of 0.85% (CI: 95%, 0.64-1.08) for Spain, 4 but lower than those reported in other studies.…”
Section: Discussionmentioning
confidence: 99%